(untitled) (Research, Society and Development, 2021)
Labor is a set of physiological changes, uterine contractions of increasing intensity and frequency that result in progressive dilation of the cervix and descent of the fetal presentation that occur within a period of time and aim at the birth of the fetus. Thus, the pain that the mother feels during childbirth can be influenced by several factors, including: culture, anxiety, fear, preparation for childbirth and support offered during this process. This study aimed to describe, based on current scientific evidence, the main non-pharmacological methods for pain relief during labor. This is an integrative literature review, where the following question was formulated: “What aspects are related to cases of pain relief in labor using non-pharmacological methods?”. The methodology used used the PICO strategy, being operationalized through the electronic search of articles indexed in PUBMED and BIREME, to identify scientific articles published in the period from 2015 to 2020, in Portuguese, Spanish and English. The search followed the pre-established inclusion criteria resulting in a total of 12 articles. In relation to non-pharmacological methods for pain relief during labor, it was observed that these methods used during labor are effective. Since these methods are an important means of conduct for health care, not only for the potential benefits they bring, but also for their high incidence and prevalence of practices adopted by professionals in the work environment, in which making it an act of humanization. And the studies showed a trend towards a higher incidence of the application of these methods, given that they contribute to the alleviation of suffering and, consequently, to the strengthening of more humane strategies in the care of parturients.